Presence of parasite larvae in goat manure for use as fertiliser - Hassan Basri, Basripuzi Nurul Hayyan; Abdullah Sani, Rehana; Omar, Mohamed Ariff; Panchadcharam, Chandrawathani (Universiti Putra Malaysia Press, 2013)
Some livestock farmers utilise goat manure to fertilise grasses grown for animal feed, which may lead to parasitic diseases caused by strongyle infection. Therefore, the presence of strongyle larvae in manure needs to be determined. In this study, goat faeces containing strongyle eggs were deposited into five replicates for daily sampling throughout 23 days and subjected to faecal egg count, larvae identification and enumeration. Absence of eggs was detected on Day 4 when the infective larvae of Haemonchus contortus, Trichostrongylus sp. and Oesophagostomum sp. were found. Larvae counts reached a maximum of 164 larvae on Day 8 and were negligible by Day 14, by which time the manure can be used as fertiliser to grow forage crops for animal feed.